Uji Aktivitas Antimalaria in vitro dari Ekstrak Etanol Batang Tanaman Ashitaba (Angelica keiskei [Miq.] Koidz) - Alvi Kusuma Wardani; Abdul Rahman Wahid; Yanti Astuti (Fakultas Farmasi Universitas Pancasila, 2020)
Malaria infection is still become a serious and complex health problem in the world. The diffi culty in treating malaria is caused by the resistance of the malaria parasite to synthetic drugs. One alternative to prevent resistance is to use herbal medicines such as the Ashitaba plant (Angelica keiskei [Miq.] Koidz). This study aims to determine the activity of Ashitaba stem ethanol extract as an antimalarial to the Plasmodium falciparum parasite strain 3D7. Ashitaba stem extract was tested for chemical compound content and antimalarial activity against Plasmodium falciparum strain 3D7 with concentrations of 100, 10, 1, 0.1 and 0.01 μg / ml. The test results for the chemical compounds of Ashitaba stem extract were positive for fl avonoids and chalcone compounds. Ashitaba stem extract with a concentration of 100, 10, 1, 0.1 and 0.01 μg / ml had an average resistance value of 67.75%, 46.61%, 32.56%, 19.60%, and 7.56%. The antimalarial activity test results of Ashitaba stem ethanol extract had an IC50 value of 11.07 μg / ml. The antimalarial activity of Ashitaba stem ethanol extract is included in the category of good antimalarial activity because the IC50 value falls within the range of 10-50 μg / ml.